A new species and a new record of Aulacus Jurine (Hymenoptera, Aulacidae) from the North Andean block with a key to Colombian species - Santos, Eduardo Fernando Dos; H., Luis A. Mazariegos (Zootaxa, 2024)
A new species of Aulacus Jurine from the Colombian Andes, A. gracielae Santos & Mazariegos sp. nov., is described. In addition, we present a new record of A. costaricensis Smith, expanding its geographical distribution. Furthermore, we present an updated identification key for the species recorded from Colombia.